Intermediates in adenovirus assembly. - Edvardsson, B (1976)
Three intermediates in adenovirus assembly have been defined; nuclear intermediates, young virions, and mature virions. The nuclear intermediates are fragile and heterogenous in size (550S-670S) and withstand separation on ficoll gradients but fall apart upon CsCl gradient centrifugation unless prefixed with glutaraldehyde. They contain both capsid and core structures, and the core structures are preferentially released during purification in CsCl. The precursor polypeptides pVI and pVII are present in the intermediates without any corresponding mature polypeptide. The young virions (Ishibashi and Maizel, 1974) are stable and preferentially confined to the nuclei after cell fractionation. They contain both uncleaved precursor polypeptides and their cleavage products. The mature virions accumulate in the cytoplasm during cell fractionation and contain the final mature polypeptides. Pulse-chase labeling kinetics, focusing on the precursor polypeptides, suggest that these three classes participate in assembly of adenovirus. Tryptic peptide maps establish that polypeptide pVI is the precursor of polypeptide VI, but only a small fraction of polypeptide 26K can in vivo account for polypeptide VIII.